Jurnalul berlinez al Norei Iuga – o ego-grafie sui generis - Simona Antofi (Revista de Istorie și Teorie Literară)
Nora Iuga’s diary written in Berlin displays an ego-graphic construction within which the spatial profile of the city – the great love of the author herself – is re-shaped through a discourse that voices the experience of facing the West, the identity and the meaning of the writer’s status, her feelings, enthusiasm and life. Thus, the text is punctually redefined according to the ever transforming ego whose identity is mirrored in the writing itself. Used as a compatibility mechanism to reality, ‘reading oneself’ by means of the feelings experienced by the ‘wanderer’ in the great city (who, by the way, has Latin blood) means that the text enhances subjective marks defined as basic mechanism of living, also in the real world.